2019
DOI: 10.4293/jsls.2019.00032
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Laparoscopic Colon Surgery in the Texas Inpatient Public Use Data File (PUDF)

Abstract: Background: Laparoscopic surgery has become the standard of care for the most common surgical procedures performed. However, laparoscopic techniques have not reached this same penetrance in colorectal surgery. We wanted to determine the percentage of colon operations performed in Texas that were done via laparoscopic, robotic and open techniques. Methods: The Texas Inpatient Public Use Data File (PUDF) was queried using ICD-9-CM diagnostic and procedure codes to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Several studies have shown that robotic-assisted colon surgery is associated with a significantly higher cost of care compared to conventional laparoscopy [ [42] , [43] , [44] , [45] , [46] ], predominantly due to its longer procedure times [ 44 , 45 ]. A propensity score–matched analysis using a nationwide hospital record database including 531,536 patients undergoing surgical treatment for colon cancer determined that robotic-assisted surgery was associated with a 13.6% higher cost than laparoscopic surgery ( P < .0001) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that robotic-assisted colon surgery is associated with a significantly higher cost of care compared to conventional laparoscopy [ [42] , [43] , [44] , [45] , [46] ], predominantly due to its longer procedure times [ 44 , 45 ]. A propensity score–matched analysis using a nationwide hospital record database including 531,536 patients undergoing surgical treatment for colon cancer determined that robotic-assisted surgery was associated with a 13.6% higher cost than laparoscopic surgery ( P < .0001) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These figures do not factor in the $1.55 million investment for the robot and its annual service contract ranging from $80,000 to $190,000 [ 47 , 48 ]. Adoption of robotic-assisted surgery is trending higher than conventional laparoscopic surgery despite its higher cost and comparable outcomes to conventional laparoscopic surgery [ [42] , [43] , [44] , [45] , [46] , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to colorectal resections, robotic techniques have been practiced since 2001 and has even been proven to be as effective and safe as its laparoscopic counterpart. Based on the current research, robotic surgery further shortens the length of hospital stay compared to laparoscopic surgery [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, coronary artery bypass grafting costs $76,384 in the United States, $17,667 in Germany, and a mere $7,323 in Korea. In the United States, the average cost of a colectomy is approximately $75,741, while in Korea, the average cost is $5,325, inclusive of government reimbursements [6,7]. Additionally, hospitals incur separate instrumental costs, which are not covered under the reimbursement In short, providing essential medical care, leads to financial losses for hospitals.…”
mentioning
confidence: 99%